If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (z + 2)(4z + -3) = 0 Reorder the terms: (2 + z)(4z + -3) = 0 Reorder the terms: (2 + z)(-3 + 4z) = 0 Multiply (2 + z) * (-3 + 4z) (2(-3 + 4z) + z(-3 + 4z)) = 0 ((-3 * 2 + 4z * 2) + z(-3 + 4z)) = 0 ((-6 + 8z) + z(-3 + 4z)) = 0 (-6 + 8z + (-3 * z + 4z * z)) = 0 (-6 + 8z + (-3z + 4z2)) = 0 Combine like terms: 8z + -3z = 5z (-6 + 5z + 4z2) = 0 Solving -6 + 5z + 4z2 = 0 Solving for variable 'z'. Factor a trinomial. (-2 + -1z)(3 + -4z) = 0Subproblem 1
Set the factor '(-2 + -1z)' equal to zero and attempt to solve: Simplifying -2 + -1z = 0 Solving -2 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1z = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1z = 0 + 2 -1z = 0 + 2 Combine like terms: 0 + 2 = 2 -1z = 2 Divide each side by '-1'. z = -2 Simplifying z = -2Subproblem 2
Set the factor '(3 + -4z)' equal to zero and attempt to solve: Simplifying 3 + -4z = 0 Solving 3 + -4z = 0 Move all terms containing z to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4z = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4z = 0 + -3 -4z = 0 + -3 Combine like terms: 0 + -3 = -3 -4z = -3 Divide each side by '-4'. z = 0.75 Simplifying z = 0.75Solution
z = {-2, 0.75}
| A=2+3t | | 5x+4+11x=180 | | f(t)=4t-4 | | X^4+5x^2=24 | | (g-7)(9g-8)= | | d(2d-1)(3d+2)(8-d)=0 | | 4x+6+7x-7+20x-11=360 | | -4y+x=13 | | (d+9)(d+8)= | | =23+k | | (x-6)+5x=90 | | 217=7(1-5v) | | (5p-3)(4-p)(8p+1)=0 | | 7x+12+6x+13x-16=360 | | 5x^2-20=3x^2-60 | | a^2+4b^2= | | =-2(m+1) | | -12-15-b=1(b+48) | | y=2.5x+4.25 | | 3(x-4)=66*11 | | ?d=5 | | 5z-z+3= | | 4x+159=2x+153 | | 35-17=3x-6 | | -8-12=20 | | 18+3x-x^2=0 | | 33x-9=90 | | (-2w)(2w-3)(3w+10)=0 | | 4x^2-33x+48=-4x+3 | | 3(5c-3)-2=13c+1 | | 4x(2x+y)= | | 6x+21=90 |